2017
DOI: 10.1111/ijfs.13574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sugar concentration on mango wine composition fermented by Saccharomyces cerevisiae MERIT.ferm

Abstract: SummaryThis study investigated the effect of initial sugar concentrations (°Brix of 17, 23 and 30) on mango wine composition fermented by Saccharomyces cerevisiae MERIT.ferm. It was found that growth rate and maximum cell population were inversely correlated with initial sugar levels with the fastest growth rate and largest cell population in the low sugar fermentation. However, the cell population in the low and medium sugar fermentation declined significantly (from 8.7 and 8.2 log to 2 and 2.8 log, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…; Lu et al . ; Viana et al . ), the concentration and quantity of chemicals are generally higher in overripe and fermented fruits than in fresh ripening fruit due to the infection of microorganisms (Beaulieu et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Lu et al . ; Viana et al . ), the concentration and quantity of chemicals are generally higher in overripe and fermented fruits than in fresh ripening fruit due to the infection of microorganisms (Beaulieu et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, although the concentration of chemicals produced during fermentation can vary depending on yeast strain, initial concentration of sugar in the fruit, and type of fruit or wine (Coelho et al 2015;Lu et al 2018;Viana et al 2008), the concentration and quantity of chemicals are generally higher in overripe and fermented fruits than in fresh ripening fruit due to the infection of microorganisms (Beaulieu et al 2017;Levey 2004;Palanca et al 2013;Rodriguez et al 2013). In particular, when ripe fruits undergo an overripening process, yeast that infects the fruit plays important role to produce large amounts of ethanol, acetic acid, and 2-phenylethnaol via fermentation (Levey 2004;Palanca et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…; Lu et al . ). Our recent study revealed that D. melanogaster showed a high tolerance to the chemicals emitted during fermentation (Kim et al .…”
Section: Introductionmentioning
confidence: 97%
“…Microbial strategies have attracted an increasing attention in wine‐making from various fruits, that is grape, pomegranate, apple, mango, and grains including polished glutinous rice and maize (Chang, Jang, Lin, & Duan, ; Lim, Jeong, & Shin, ; Lu, Chan, Li, & Liu, ). The levels of volatile compounds and their health benefits have been enhanced in the wine of Korean black raspberry Rubus coreanus Miq.…”
Section: Introductionmentioning
confidence: 99%
“…The fermentation process combined with UV‐B treatment had considerably enhanced the nutritional value in the fermented leaves of white cabbage (Harbaum‐Piayda, Palani, & Schwarz, ), polyphenolics in black tea (Kerio, Wachira, Wanyoko, & Rotich, ), and antioxidant capacity of yellow tea (Gramza‐Michałowska et al., ). In addition, Lu reported highest levels of volatile compounds notably ethyl esters, acetate esters, and isoamyl alcohol in mango wine (Lu et al., ).…”
Section: Introductionmentioning
confidence: 99%